Modelli spaziali dell'evoluzione dei territori turistici - Enza Zabbini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
– This paper explain the geographical interpretation of the touristic phenomena. Tourism becomes an important sector which involves the territorial organisation in different ways. The attention of geography is growing with the enlargement of the effects that tourism causes to different scales, local and global. The approach changes from statics model to dynamics interpretation where more and more variables are involved in the process.
Keywords: 330